Menilik Nazar Dalam Kajian Dogmatis Serta Relevansinya Bagi Jemaat Huria Kristen Indonesia - Puspita Sari Panjaitan, Angria; Munthe, Pardomuan (Shift Key : Jurnal Teologi dan Pelayanan, 2025)
The practice of making vows has been found to potentially deviate from its authentic theological meaning among members of the Huria Kristen Indonesia (HKI) Special Resort Tarutung. Preliminary observations indicate that some congregants tend to understand vows in a transactional manner, perceiving them as a form of "bargaining" with God. This study aims to examine the concept of vows from a dogmatic theological perspective and to analyze its relevance for the HKI congregation. The research employs a mixed-methods approach, utilizing questionnaires administered to 45 respondents and in-depth interviews with five key informants. The findings reveal that 93% of respondents have made vows and 97% believe that vows influence their relationship with God; however, only 20% consistently fulfill the vows they have made. This indicates a significant gap between commitment and practice. The study concludes that the relevance of understanding vows for the HKI congregation lies in the importance of cultivating a proper attitude of faith in relationship with God, in which congregants are encouraged not to treat vows as obligations or transactions, but to express gratitude to God through Faith Commitments that arise from obedience and sincere service.